Malay Cultural Resistance In Pekanbaru City: Cultural Disruption Towards A Urban Expansion - Rahmah, Sitti; M. Rifqi Romadhona; Fitra Al Hadro; Sukma Erni (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
This research investigates the resistance of Malay culture in Pekanbaru City in response to cultural disruption on its path toward becoming a megapolitan city. In this context, the influence of technology has proven to play a significant role in altering how the Malay community in Pekanbaru carries out their traditions. However, this study also identifies a series of efforts undertaken to support the vision and mission of Pekanbaru City in preserving and promoting Malay culture. These strategies involve the development of city tourism that incorporates educational and cultural publication aspects of Malay culture, the preservation of Malay culture through an academic approach via educational institutions and libraries, and the use of the Malay language in local regulations as a concrete step in maintaining culture in everyday life. This research is a qualitative study that relies on observation, interviews, documentation studies, and interactions with stakeholders in Pekanbaru City to gain a deep understanding of the resistance of Malay culture amidst the ongoing cultural transformation.